Osteoporosis in Cervical Spine Surgery. Issue 8 (April 2016) - Guzman, Javier Z.; Feldman, Zachary M.; McAnany, Steven; Hecht, Andrew C.; Qureshi, Sheeraz A.; Cho, Samuel K.
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: Retrospective administrative database analysis. Objective: To investigate the effect of osteoporosis (OS) on complications and outcomes in patients undergoing cervical spine surgery. Summary of Background Data: OS is the most prevalent degenerative human bone disease, and spine surgeons will inevitably perform procedures on patients with OS. These patients might present a difficult patient cohort because many fixation techniques depend on bone quality and adequate bone healing—both of which are compromised in OS. Methods: The nationwide inpatient sample was queried using the Ninth Revision, Clinical Modification procedural codes for cervical spine procedures and diagnosis codes for degenerative conditions of cervical spine from 2002 to 2011. Patients were separated into two cohorts, those patients with OS and those without OS. Demographics, hospital characteristics, and adjusted complication likelihood were analyzed. Multivariate regression analysis was performed to determine odds of revision surgery in patients with OS. Results: Of all patients undergoing degenerative cervical spine surgery, 2% were identified as having OS (32, 557 of a sample of 1, 602, 129 patients). Osteoporotic patients were more likely to undergo posterior cervical spine fusion when compared with those patients without OS (11.3% vs. 5.4%, P < 0.0001). Moreover, circumferential fusion was performed 3 times more frequently in the osteoporotic cohort. Adjusted complications showed increased odds for postoperative hemorrhage (odds ratio = 1.70, 95% confidence interval = 1.46–1.98, P < 0.0001). Patients with OS stayed in the hospital longer (3.5 vs. 2.5 days, P < 0.0001) and had 30% costlier hospitalizations. Multivariate for revision surgery indicated that osteoporotic patients had significantly increased odds of revision surgery (odds ratio = 1.54, P ≤ 0.0001) when referenced to non-osteoporotic patients undergoing cervical spine surgery. Conclusion: Osteoporotic patients were more likely to undergo revision surgery, have longer hospitalizations, and have higher hospitalization costs, than their non-osteoporotic counterparts. Level of Evidence: 3